Enterprise Liability and the Common Law - Nolan, D (Oxford University Press, 2012)
This book is a timely account of the relationship between the theory of ‘enterprise liability’ and a number of common law doctrines, principally vicarious liability. The account is timely because the dust has now begun to settle on the 1999 decision in Bazley v Curry, where the Supreme Court of Canada reformulated the law relating to the course of employment by seeking to put it on an ‘enterprise liability’ footing, a decision which in turn influenced the House of Lords’ approach to the same issue in Lister v Hesley Hall Ltd. According to the book’s author, Douglas Brodie, the invocation of enterprise liability can be seen as the common law’s response to contemporary concerns over the proper extent of corporate social responsibility, a claim he seeks to substantiate by a wide-ranging analysis of the inter-relationship between enterprise liability and the common law which is not limited to UK law but also makes extensive reference to authorities from Australia, Canada and the USA.